Dynamics and vertical distribution of a Hrabeiella periglandulata (Annelida) population in South Moravia, Czech Republic - Schlaghamersky, Jiri; Šídová, Adéla (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the density, dynamics and vertical distribution of a Hrabeiella periglandulata population in a forest soil at Brno, Czech Republic. From December 2003 to November 2004, two plots covered by mixed stands and two covered by coniferous stands were sampled monthly. Six soil cores per plot were taken down to 15 cm and subdivided into layers, which were subjected to wet funnel extraction. Missing in one of the coniferous stands H. periglandulata was abundant in the mixed stand with the highest soil pH. In this stand, monthly sampling continued until November 2005, with three additional samplings up to January 2007. Mean annual density was 2,672±1,534 individuals m-2. Population dynamics differed from those reported from Germany. Highest densities were reached in early summer, lowest between August and December. Due to aggregated horizontal distribution, differences between monthly values were often nonsignificant. No significant correlation with climatic data was found. Nevertheless, the observed dynamics corresponded to the climatic conditions, showing particularly the negative effect of drought. The population was evenly distributed in the sampled soil profile, only avoiding the organic layer. Except for a locality in Poland, this is the easternmost record of the species.